2017
DOI: 10.1016/j.ajo.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

The ISNT Rule: How Often Does It Apply to Disc Photographs and Retinal Nerve Fiber Layer Measurements in the Normal Population?

Abstract: Purpose To determine what percentage of normal eyes follow the ISNT rule, and whether ISNT rule variants may be more generalizable to the normal population. Design Cross-sectional study. Methods Setting: Institutional setting. Study Population: 110 normal subjects. Observation Procedures: Neuroretinal rim assessments from disc photos and RNFL thickness measurements from spectral domain OCT. Main Outcome Measures: The percentages of subjects that obeyed the ISNT rule and its variants. Results The ISNT rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 44 publications
4
34
1
5
Order By: Relevance
“…Recent studies have attempted to answer this question and observed that, contrary to clinical wisdom, the rule is more often than not disobeyed even in healthy eyes. 5 Our results echo this sentiment in eyes with emmetropia or low myopia, showing that the problem may be compounded in eyes suffering from higher myopia. This finding supports another recent study published on a large myopic cohort.…”
Section: Thickness Of Papillary and Peripapillary Nerve Fiberssupporting
confidence: 80%
See 1 more Smart Citation
“…Recent studies have attempted to answer this question and observed that, contrary to clinical wisdom, the rule is more often than not disobeyed even in healthy eyes. 5 Our results echo this sentiment in eyes with emmetropia or low myopia, showing that the problem may be compounded in eyes suffering from higher myopia. This finding supports another recent study published on a large myopic cohort.…”
Section: Thickness Of Papillary and Peripapillary Nerve Fiberssupporting
confidence: 80%
“…This rule is often violated in the healthy eye for both neuroretinal rim and peripapillary RNFL measures; however, variations such as IST and IS are obeyed in a majority of patients. 5 In myopia, concordance with the ISNT rule may be even less prevalent, with a recent study reporting concordance of only 12% with the ISNT rule for RNFL thickness. 6 This agrees with other studies that have shown changes in the position of peak thickness of the peripapillary RNFL in myopia.…”
mentioning
confidence: 99%
“…The selected features for OD and OD-cup identification were: cup-to-disc ratio (CDR), neuroretinal rim (NRR) area, blood vessel area and the ISNT rule. More details about CDR, NRR, and ISNT rule can be found in the works of Hu et al, Mabuchi et al, Jonas et al and Poon et al [41][42][43][44]). Moreover, the SVM, the function kernel RBF, and the Artificial Neural Network (ANN) were used as classifications.…”
Section: Methods Using Features Extraction For Glaucoma Diagnosismentioning
confidence: 99%
“…The sudden or abrupt diminishing of NRR thickness indicates the presence of a notch. Notch is major sign of glaucoma, even though the CDR may be within normal limits [11][12][13]. ISNT rule is generally true for most of the ODs.…”
Section: Fig 1 Anatomy Of Eye Showing Optic Nerve Headmentioning
confidence: 99%
“…3 shows a healthy optic disc, having ISNT rule intact. The latest study by Linda Yi-Chieh Poon, et al, proposes to use IST and IS rule instead of ISNT rule, for better glaucoma diagnosis [13].…”
Section: Fig 1 Anatomy Of Eye Showing Optic Nerve Headmentioning
confidence: 99%